Investments in innovations of social and technological enterprises - K. B. Gerasimov (Вестник университета)
The modern literature extensively considers the process of technological innovations and the results of the activities of market-oriented organizations. However, there are no studies of the process of technological innovations and the results of socio-technological enterprises that are formed to create social value through the use of technologies. The paper presents a conceptual model of how the investments of socio-technological enterprises in technological innovations implemented in the process of innovation implementation affect their market and social strategic orientation. The author considers these investments in innovations at four levels of analysis: founders, innovations, organization, and the external environment. The presented model and proposals promote and enrich the current literary sources regarding the factors that affect the balance of the strategic orientation of socio-technological enterprises between the social and market orientation.